2022
DOI: 10.1186/s12885-022-09463-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle biomarkers for pancreatic cancer diagnosis: a systematic review and meta-analysis

Abstract: Background Extracellular vesicle (EV) biomarkers have promising diagnosis and screening capacity for several cancers, but the diagnostic value for pancreatic cancer (PC) is controversial. The aim of our study was to review the diagnostic performance of EV biomarkers for PC. Methods We performed a systematic review of PubMed, Medline, and Web Of Science databases from inception to 18 Feb 2022. We identified studies reporting the diagnostic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…In addition, six types of pancreatic cancer-associated miRNAs , (miRNA-21, miRNA-16, miRNA-10b, miRNA-155, miRNA-1246, and miRNA-196a) were chosen as models to evaluate the capability of encoded fusion-mediated multiplex detection by a panel of ETFBs containing the corresponding MBs (Table S2). The specificity of these MBs was satisfactory (Figure S14).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, six types of pancreatic cancer-associated miRNAs , (miRNA-21, miRNA-16, miRNA-10b, miRNA-155, miRNA-1246, and miRNA-196a) were chosen as models to evaluate the capability of encoded fusion-mediated multiplex detection by a panel of ETFBs containing the corresponding MBs (Table S2). The specificity of these MBs was satisfactory (Figure S14).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Consistent with previous reports, the expression levels of these six types of tEVs-miRNAs were higher in pancreatic cancer patients than in healthy donors and pancreatitis patients. 8,40 Moreover, the diagnostic accuracy of the sum of six types tEV-miRNAs (98%) was higher than that of a single tEV-miRNA (73% for miRNA-155 as an example), indicating that multiplex detection has advantages in improving the diagnostic accuracy of pancreatic cancers (Figure 4D). Collectively, the ETFB-based encoded fusion strategy is a feasible tool for the clinical diagnosis of pancreatic cancer and can improve diagnostic accuracy due to its multiplex detection capability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A study involving 139 patients with early stage pancreatic, ovarian, or bladder cancer demonstrated an area under the curve of 0.95 (sensitivity 71.2%, specificity 99.5%) using an extracellular vesicle protein-based diagnostic blood test [ 25 ]. A meta-analysis of 39 studies on pancreatic cancer concluded that EV RNAs were effective biomarkers for pancreatic cancer screening with 79% sensitivity and 87% specificity, even at its rudimental stage [ 52 ]. When combining both protein and RNA biomarkers, they came to an excellent diagnostic performance of 90% sensitivity and 94% specificity for stage I and II pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In systematic review reports, several markers have been labelled as promising, yet remain under investigation for clinical utility. Extracellular vesicle (including microRNAs and others) as biomarkers have been scrutinized, 60 yet technological difficulties and standardization needs to be overcome before translation into clinical use.…”
Section: Biomarkers For Early Detection Of Pdacmentioning
confidence: 99%